Encountering the 'unexpected' in phenomenological research. Faith and belief as expressions of spirituality in a qualitative study. Issue 3 (2nd October 2017) - Natsis, Eva
Abstract: A study of 12 secondary schools students in Victoria, Australia explored the spirituality of young people in the context of their everyday lives through a hermeneutic phenomenological investigation. In developing an understanding of what spirituality meant to the participants in this study, it was apparent that spirituality was deeply abiding and embedded within the participants' religious traditions. This was influenced by the exposure participants had to religious and spiritual teachings. Despite the fact that the participants expressed a range of religious beliefs about God, the afterlife and transcendence towards others as significant ways in which they understood spirituality, the findings were not generalisable across the Australian population. These themes will be explored throughout the paper proving implications for educators working with specific groups of students from faith backgrounds and the possibility of investigating what young people from non-religious backgrounds believe.